Thermodynamic Assessment of Different Feedstocks Gasification Using Supercritical Water and CO2 for Hydrogen and Methane Production - Luis David García Caraballo; Julles Mitoura dos Santos Junior; Icaro Augusto Maccari Zelioli; York Castillo Santiago; Juan F. Perez Bayer; Adriano Pinto Mariano (Eng)
The supercritical water gasification (SCWG) and carbon dioxide gasification of agro-industrial and urban waste residues—Coffee Husk, Eucalyptus Biochar, Energy Sugarcane, and Refuse-Derived Fuel (RDF)—were studied using TeS® v.2 software, which employs a non-stoichiometric thermodynamic model to minimize Gibbs free energy and predict equilibrium compositions. The effects of temperature (873.15–1273.15 K), pressure (220–260 bar), biomass feed (18–69%), and gasifying agents on hydrogen and methane formation were analyzed. Higher temperatures and biomass feed percentages favored hydrogen production, while lower temperatures increased methane formation. At 1273.15 K, RDF showed the highest hydrogen yield in SCWG, rising from 0.43 to 1.42 mol, followed by Energy Sugarcane (0.39 to 1.23 mol), Coffee Husk (0.34 to 0.74 mol), and Eucalyptus Biochar (0.33 to 0.62 mol). In CO2 gasification, hydrogen yields were lower but followed a similar trend. At 873.15 K, RDF also exhibited the highest methane increase in SCWG, from 0.14 to 0.91 mol, followed by Energy Sugarcane (0.12 to 0.65 mol), Coffee Husk (0.11 to 0.36 mol), and Eucalyptus Biochar (0.11 to 0.29 mol). Methane formation in CO2 gasification was significantly lower, with RDF increasing from 0.0035 to 0.35 mol, followed by Energy Sugarcane (0.0024 to 0.24 mol), Coffee Husk (0.0002 to 0.058 mol), and Eucalyptus Biochar (0.0002 to 0.028 mol). On the other hand, a slight increase in hydrogen formation was observed as pressure decreased, while the opposite effect was observed for methane formation, with a small increase in its production as pressure increased. The impact of pressure change on the equilibrium compositions was not as significant as the effect observed by varying temperature; this behavior was observed in both gasification processes studied. Additionally, the behavior of the H2/CO molar ratio for each biomass in the studied gasification processes was analyzed to assess the potential uses of the produced syngas. It was observed that the SCWG resulted in significantly higher H2/CO molar ratios compared to CO2 gasification.